A new genus of Gyponini (Hemiptera, Cicadellidae, Iassinae) with description of two new species from Brazil and key to genera of the Hecalapona complex - Domahovski, Alexandre Cruz; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2024)
Gracilipona gen. nov. is described and illustrated based on males and females of two new species from Brazil: G. tetrarama sp. nov. (type-species) from the states of Minas Gerais, Paraná, Rio de Janeiro, and Rio Grande do Sul, and G. birama sp. nov. from Bahia State. The new genus differs from other genera of the Hecalapona complex as follows: antennal ledge extending anteriorly below anterior margin of crown, forming an arched carina that connects the antennal ledges medially; pronotum moderately declivous; forewing with extra crossveins on distal third; protibia with dorsal surface flattened but not expanded, with lateral margins carinate; aedeagus with dorsal apodemes strongly developed and divergent and shaft with lateral processes arising from basal third; ovipositor with valvulae expanded subapically; first valvula with dorsal sculptured area short, mostly strigate, areolate near dorsal margin; and second valvula with a few rounded denticles subapically on dorsal margin. An updated key to genera of the Hecalapona complex and a discussion comparing Gracilipona gen. nov. with other related genera are provided.